Pemanfaatan Teknologi Informasi, Kesesuaian Tugas dan Kinerja Karyawan Lembaga Perkreditan Desa - Indah Gita Cahyani, Putu Krishnadewi; Mertha, Made (E-Jurnal Akuntansi; Vol 33 No 6 (2023), 2023)
The development of the company really needs to be supported by the performance of its employees. To determine how information technology can lead to desired results or performance, it is important to understand the relationship between information technology use and outcomes. This research was conducted to obtain empirical evidence of the influence of information technology utilization and task suitability on employee performance. The sample technique in this study used purposive sampling by obtaining 40 samples. The data from the study were obtained by means of a questionnaire. The research uses multiple linear regression analysis techniques that have previously passed testing against classical assumptions. The results showed a significant positive effect between the use of information technology and task suitability on the performance of Village Credit Institution (LPD) employees. Keywords: Employee Performance, Utilization of Information Technology, Job Suitability, LPD